2005
DOI: 10.1177/154405910508401007
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Stem Cells from Cryopreserved Periodontal Ligament

Abstract: Human post-natal stem cells possess a great potential to be utilized in stem-cell-mediated clinical therapies and tissue engineering. It is not known whether cryopreserved human tissues contain functional post-natal stem cells. In this study, we utilized human periodontal ligament to test the hypothesis that cryopreserved human periodontal ligament contains retrievable post-natal stem cells. These cryopreserved periodontal ligament stem cells maintained normal periodontal ligament stem cell characteristics, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
151
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(163 citation statements)
references
References 20 publications
8
151
0
4
Order By: Relevance
“…The results of the transplantations showed a significant improvement of periodontal diseases, suggesting that PDLSC transplantation could be a safe and promising treatment for clinical periodontitis (Feng et al, 2010). Furthermore, it has been reported that human PDLSCs recovered from cryopreserved human PDL tissue maintained normal PDLSC characteristics, including expression of STRO-1, single-colony-strain generation, multipotency and cementum/PDL-like tissue generation, providing a possible and practical clinical approach for the utilization of PDLSCs isolated from frozen PDL tissues (Seo et al, 2005). These findings demonstrate that PDLSCs not only possess stem cell characteristics, including self-renewal, multipotency and immunomodulatory properties similar to BMMSCs, but also hold a unique potential to fabricate three-dimensional PDL tissue.…”
Section: Characteristics Of Pdl Stem Cellsmentioning
confidence: 99%
“…The results of the transplantations showed a significant improvement of periodontal diseases, suggesting that PDLSC transplantation could be a safe and promising treatment for clinical periodontitis (Feng et al, 2010). Furthermore, it has been reported that human PDLSCs recovered from cryopreserved human PDL tissue maintained normal PDLSC characteristics, including expression of STRO-1, single-colony-strain generation, multipotency and cementum/PDL-like tissue generation, providing a possible and practical clinical approach for the utilization of PDLSCs isolated from frozen PDL tissues (Seo et al, 2005). These findings demonstrate that PDLSCs not only possess stem cell characteristics, including self-renewal, multipotency and immunomodulatory properties similar to BMMSCs, but also hold a unique potential to fabricate three-dimensional PDL tissue.…”
Section: Characteristics Of Pdl Stem Cellsmentioning
confidence: 99%
“…The enlargement of epithelial rests of Malassez in the cryopreserved teeth after transplantation in rat abdomen was shown to be the result of inflammation and cryoprotectant (Kawasaki et al, 2004). Seo et al showed the normal histological structure of periodontal ligament after the cryopreservation in liquid nitrogen for three and six months (Seo et al, 2005). No positive terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining was observed (Seo et al, 2005).…”
Section: Biological Responses Of Cryopreserved Teeth Periodontal Ligamentioning
confidence: 99%
“…Seo et al showed the normal histological structure of periodontal ligament after the cryopreservation in liquid nitrogen for three and six months (Seo et al, 2005). No positive terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining was observed (Seo et al, 2005).…”
Section: Biological Responses Of Cryopreserved Teeth Periodontal Ligamentioning
confidence: 99%
See 1 more Smart Citation
“…The potential use of dental stem cells has become even more viable for tissue regeneration and other therapies with the recent advances in cryopreservation. These advances allow proliferation and long term storage of these cells for future cell therapy treatments while maintaining their differentiation potential (Ding et al, 2010;Papaccio et al, 2006;Seo et al, 2005;Woods et al, 2009;Zhang et al, 2006).…”
Section: Dental Stem Cells In Tissue Engineering and Regenerative Medmentioning
confidence: 99%